125 problems in text algorithms : with solutions - Crochemore, Maxime, 1947-; Lecroq, Thierry; Rytter, Wojciech (Cambridge : Cambridge University Press, 2021)
String matching is one of the oldest algorithmic techniques, yet still one of the most pervasive in computer science. The past 20 years have seen technological leaps in applications as diverse as information retrieval and compression. This copiously illustrated collection of puzzles and exercises in key areas of text algorithms and combinatorics on words offers graduate students and researchers a pleasant and direct way to learn and practice with advanced concepts. The problems are drawn from a large range of scientific publications, both classic and new. Building up from the basics, the book goes on to showcase problems in combinatorics on words (including Fibonacci or Thue-Morse words), pattern matching (including Knuth-Morris-Pratt and Boyer-Moore like algorithms), efficient text data structures (including suffix trees and suffix arrays), regularities in words (including periods and runs) and text compression (including Huffman, Lempel-Ziv and Burrows-Wheeler based methods).
Title from publisher's bibliographic system (viewed on 11 Jun 2021).
Keywords: Text processing (Computer science) -- Problems, exercises, etc; Computer algorithms -- Problems, exercises, etc